Design of new phenothiazine derivatives as visible light photoinitiators. Issue 19 (6th May 2020) - Rahal, Mahmoud; Abdallah, Mira; Bui, Thanh-Tuân; Goubard, Fabrice; Graff, Bernadette; Dumur, Frédéric; Toufaily, Joumana; Hamieh, Tayssir; Lalevée, Jacques
Abstract : In this article, four new phenothiazine derivatives (denoted as PT1, PT2, PT3 and PT4 ) are specifically in silico designed by molecular modelling for good light absorption properties @405 nm. Abstract : In this article, four new phenothiazine derivatives (denoted as PT1, PT2, PT3 and PT4 ) are specifically in silico designed by molecular modelling for good light absorption properties @405 nm. The most interesting structures showing both intense violet/blue light absorption and high potential photochemical reactivity were synthesized for detailed investigations as photoinitiators/photosensitizers in the presence of an iodonium salt for the free radical photopolymerization of (meth)acrylates and the cationic polymerization of epoxides upon near-UV or visible light irradiation. Remarkably, two of the proposed structures (PT3 and PT4 ) from this in silico design were never synthesized prior to this work and were thus specifically designed for this work. Three-component photoinitiating systems based on PT/iodonium/amine ( N -phenylglycine or ethyl 4-dimethylaminobenzoate) are also developed for the free radical polymerization of acrylates. Both excellent polymerization rates and high final reactive function conversions were obtained. A full picture of the photochemical mechanisms is provided using different techniques: real-time Fourier transform infrared spectroscopy, UV-visible spectroscopy, fluorescence spectroscopy, and cyclic voltammetry. Finally, the high performance of the phenothiazine derivatives is also shown in 3D printing experiments as well as in photocomposite synthesis using glass fibres (thick sample; using a LED@395 nm conveyor).